Macrolide therapy is associated with lower mortality in community-acquired bacteraemic pneumonia. (July 2018) - ,; Arnold, Forest; Peyrani, Paula; Ramirez, Julio; Ayesu, Kwabena; File, Thomas; Burdette, Steven; Blatt, Stephen; Restrepo, Marcos; Bordon, Jose; Gross, Peter; Musher, Daniel; et al.
Abstract: Background: Community-acquired pneumonia (CAP) has a potential complication of bacteremia. The objective of this study was to define the clinical outcomes of patients with CAP and bacteremia treated with and without a macrolide. Materials and methods: Secondary analysis of the Community-Acquired Pneumonia Organization database of hospitalized patients with CAP. Patients with a positive blood culture were categorized based on the presence or absence of a macrolide in their initial antimicrobial regimen, and severity of their CAP. Outcomes included in-hospital all-cause mortality, 30-day mortality, length of stay, and time to clinical stability. Results: Among 549 patients with CAP and bacteremia, 247 (45%) were treated with a macrolide and 302 (55%) were not. The primary pathogen was Streptococcus pneumoniae (74%). Poisson regression with robust error variance models were used to compare the adjusted effects of each study group on the outcomes. The unadjusted 30-day mortality was 18.4% in the macrolide group, and 29.6% in the non-macrolide group (adjusted relative risk (aRR)0.81; 95% confidence interval (CI)0.50–1.33; P  = 0.41). Unadjusted in-hospital all-cause mortality was 7.3% in the macrolide group, and 18.9% in the non-macrolide group (aRR 0.54, 95% CI 0.30–0.98; P  = 0.043). Length of stay and time to clinical stability were not significantly different. Conclusions: In-hospital mortality, but not 30-day mortality, was significantly better in the macrolide group. Our data support the use of a macrolide in hospitalized patients with CAP and bacteraemia. Graphical abstract: Highlights: Patients with community-acquired pneumonia and bacteremia have a high mortality. Mortality was significantly lower among patients who received a macrolide. The association was more significant among patients with severe pneumonia.